ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDIDIKAN KEWIRAUSAHAAN(ENTREPRENEURSHIP EDUCATION) DI PERGURUAN TINGGI NEGERI KOTA BANDUNG - Rafika Rahmadani; Suwatno Suwatno; Amir Machmud (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
This research aims to identify the factors that influence entrepreneurial education at public universities in Bandung. This study is expected to create jobs and change the mind-set of college graduates to become job creators method used in this study is a survey method. Subjects in this study are students of Universitas Pendidikan Indonesia (UPI). The samples were used that were 30 students of accounting education. Analysis of the data used in this research is the analysis of Structural Equation Model (Structural Equation Model / SEM). Average of entrepreneurship education at public universities in Bandung, especially in UPI shows that entrepreneurship education indicators ie 70.03% voted in favor of the implementation entrepreneurship education, and 82.13% consisted of 24 students who strongly agree and agree with the concept of entrepreneurial intentions while 46.30% is composed of 13 students who agree and disagree with the rest answering entrepreneurial development. These circumstances reveal the factors that affect entrepreneurship education in higher education is seen from the intention of entrepreneurship and entrepreneurial development